Geology, Metamorphism and Structural Evaluation of Precambrian Basement Rocks in El Obeid Area, Kordofan Region, Sudan - Mustafa, Hassan A; A Salih, Mushal; A Elmansour, Asim; I Abdallsamed, Mohammed; A Elhadi, Mohammed; M Slama, Einas (Journal of Advanced Research in Geo Sciences & Remote Sensing; Vol 7 No 1&2 (2020): Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
The rock units in El Obeid area comprised gneisses and migmatites covering most of the area. The Supracrustal metasediments mica schist and lenticular lenses of amphibolites overlies unconformable these gneisses and migmatites. The acidic intrusive felsite and quartzite intruded due to the regional dynamic metamorphism. The amphibolite rocks indicated different petrogenesis displaying three mineral generations confirmed the polymetamorphism. The first cycle of metamorphism represented by the oldest units, is of medium- to high-grade. This cycle associated by NW-SW, NE-SW trending fractures. The second cycle affects the pile and the Supracrustal metasediments; is of low-grade metamorphism grade. The third cycle which of dynamic nature affected all sequence units in the study area, is of greenschist facies conditions, generated the deformational shearing episode with NE-SW, NNE-SSW and rarely NW-SE and N-S trend. The relationships between the metamorphism and structures in the area appeared in the conjunction of any cycle of metamorphism with deformations in response to its grade. The structures reflected the degrees of metamorphism which gradual retrograded from medium-grade to low-grade metamorphism. How to cite this article: Mustafa HA, Salih MA, Elmansour AA et al. Geology, Metamorphism and Structural Evaluation of Precambrian Basement Rocks in El Obeid Area, Kordofan Region, Sudan. J Adv Res Geo Sci Rem Sens 2020; 7(1&2): 6-16.